Roles of DctA and DctB in Signal Detection by the Dicarboxylic Acid Transport System of Rhizobium leguminosarum - Reid, Colm J. (American Society for Microbiology (ASM), 1998)
The dctA gene, coding for the dicarboxylate transport protein, has an inducible promoter dependent on activation by the two-component sensor-regulator pair DctB and DctD. LacZ fusion analysis indicates that there is a single promoter for dctB and dctD. The dctA promoter is also induced by nitrogen limitation, an effect that requires DctB-DctD and NtrC. DctB alone is able to detect dicarboxylates in the absence of DctA and initiate transcription via DctD. However, DctA modifies signal detection by DctB such that in the absence of DctA, the ligand specificity of DctB is broader. dctAp also responds to heterologous induction by osmotic stress in the absence of DctA. This effect requires both DctB and DctD. A transposon insertion in the dctA-dctB intergenic region (dctA101) which locks transcription of dctA at a constitutive level independent of DctB-DctD results in improper signalling by DctB-DctD. Strain RU150, which carries this insertion, is defective in nitrogen fixation (Fix(−)) and grows very poorly on ammonia as a nitrogen source whenever the DctB-DctD signalling circuit is activated by the presence of a dicarboxylate ligand. Mutation of dctB or dctD in strain RU150 reinstates normal growth on dicarboxylates. This suggests that DctD-P improperly regulates a heterologous nitrogen-sensing operon. Increased expression of DctA, either via a plasmid or by chromosomal duplication, restores control of DctB-DctD and allows strain RU150 to grow on ammonia in the presence of a dicarboxylate. Thus, while DctB is a sensor for dicarboxylates in its own right, it is regulated by DctA. The absence of DctA allows DctB and DctD to become promiscuous with regard to signal detection and cross talk with other operons. This indicates that DctA contributes significantly to the signalling specificity of DctB-DctD and attenuates cross talk with other operons.